1988
DOI: 10.1159/000116601
|View full text |Cite
|
Sign up to set email alerts
|

Central Organization of Wave Localization in the Clawed Frog, <i>Xenopus laevis</i>

Abstract: The organization of water wave localization within the midbrain of the clawed frog Xenopus was investigated by performing behavioral tests on frogs that had partial midbrain ablations. The criterion of localization was the orientation of turns toward the origin of impinging waves. All lesion effects became apparent as localization failure within an angular sector of wave direction. The sectors were contralateral to the lesion and of various sizes, some comprising the complete hemifield. Localization outside of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…If not indicated otherwise, each of the described lesion types was tested at least three times, and the results were uniform for each type. The conclusions are further corroborated by the results of a considerable number of smaller lesions, which are described in the companion paper [Elepfandt, 1988].…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…If not indicated otherwise, each of the described lesion types was tested at least three times, and the results were uniform for each type. The conclusions are further corroborated by the results of a considerable number of smaller lesions, which are described in the companion paper [Elepfandt, 1988].…”
Section: Methodssupporting
confidence: 62%
“…The present paper demonstrates that the midbrain is nec essary for wave localization and that the localization is organized in the form of a functional chiasm. In the companion paper, I describe a dual topological organization for wave localization in the midbrain [Elepfandt, 1988]. Preliminary reports have appeared elsewhere [Elepfandt, 1984b[Elepfandt, , 1986a.…”
Section: Introductionmentioning
confidence: 99%
“…1985b; Will, 1989; Edwards & Kelley, 2001). Among these nuclei, the TM possibly exhibits divisions concerned with wave source localization and frequency resolution, respectively (Elepfandt, 1988b; Reisbeck, 1994). Notably, substantial projections of the torus semicircularis reach the optic tectum (OT), where lateral line units of remarkable spatial selectivity were observed (Zittlau et al.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially at least, some of those units could match by their spatial tuning the behavioural localization accuracy of the animal (5°; Elepfandt, 1982). Behavioural tests after midbrain lesions had suggested that it is mainly the anterior extension of the TM which is involved in stimulus localization and that here wave source directions are represented in a systematic order (Elepfandt, 1988b). In this regard, the prevalence of BF classes ≤ 25 Hz in the rostral midbrain invites us to consider these frequencies to be vital for wave source localization.…”
mentioning
confidence: 99%